Consolidating the Gains and Reshaping the Future of Democracy in Nigeria - Peter B. Bisong; Asira E. Asira (PINISI Discretion Review, 2021)
Nigeria has practiced uninterrupted democracy from 1999 to date. She has however, little to show for this long practice of what was hitherto perceived as the harbinger of good things. This paper argues that the slow growth of democracy in Nigeria, has nothing to do with a defect in democracy itself, but with the nature of Nigerians. Democracy viewed on its own is good, but the way it is practiced in Nigeria has made it not to flourish. The paper recommends steps to be taken by all Nigerians, in order to consolidate democracy and to reposition it for future dividend delivery.